Ankara Moscow Confrontation in Caucasus: Türkiye’s Support to Azerbaijan in the Second Karabakh War and Strategic Acquisitions of the Duo - Turan, Ahmet (Mehmet Akif KARA, 2025)
It is a widely recognised fact in the literature that Türkiye and Russia were on opposite sides in the history of the Karabakh conflict and pursued policies based on rivalry. However, Ankara could not support Azerbaijan sufficiently in the First Karabakh War due to many restrictive factors and both Azerbaijan and Türkiye were the losers of the war. However, in the Second Karabakh War, Azerbaijan’s economic and military strengthening and changing balances ensured that the winning side was the Baku-Ankara front. In addition, one of the important factors in Azerbaijan’s victory was Türkiye’s military and diplomatic support. The aim of this study is to reveal the ways in which Türkiye’s support to Azerbaijan was manifested in the Second Karabakh War and the acquisitions of Azerbaijan’s victory in terms of Türkiye-Azerbaijan axis. In this respect, the study is important in terms of revealing Ankara’s military and diplomatic support to Baku in the Türkiye-Russia rivalry within the framework of neoclassical variables. In this context, case analysis is used in the study from one of the qualitative research methods. Within the scope of this type of research, the ways in which Türkiye and Russia confronted each other in the Second Karabakh War and the means and methods of Türkiye’s support for Azerbaijan are determined. The study concluded that there was a rivalry between Türkiye and Russia in the Second Karabakh War and that one of the main determinants of this rivalry was Türkiye’s military and diplomatic support to Azerbaijan. In this direction, the study uses primary sources such as documents published by the official authorities of the parties and the statements of high-level officials of the countries, as well as secondary sources such as other periodicals in the literature.

Karabağ meselesinin tarihçesinde Türkiye ve Rusya’nın karşıt saflarda yer alarak rekabete dayalı politikalar izlediği literatürde geniş yankı bulan bir gerçektir. Ancak Ankara Birinci Karabağ Savaşı’nda birçok kısıtlayıcı etkenlerden dolayı Azerbaycan’ı yeterince destekleyememiş ve hem Azerbaycan hem de bununla bağlantılı olarak Türkiye savaşın kaybedeni olmuşlardır. Ancak İkinci Karabağ Savaşı’nda Azerbaycan’ın ekonomik ve askeri olarak güçlenmesi ve değişen dengeler kazanan tarafın Bakü-Ankara safı olmasını sağlamıştır. Bunun yanında Azerbaycan’ın zaferindeki önemli etkenlerden biri de Türkiye’nin askeri ve diplomatik desteği olmuştur. Bu çalışmanın amacı İkinci Karabağ Savaşı’nda Türkiye’nin Azerbaycan’a desteğinin hangi yollarla tezahür ettiğini ve Azerbaycan’ın zaferinin Türkiye-Azerbaycan hattı açısından kazanımlarının neler olduğunu ortaya koymaktır. Bu kapsamda çalışma, Türkiye-Rusya rekabetinde Ankara’nın Bakü’ye verdiği askeri ve diplomatik desteği neoklasik değişkenler çerçevesinde ortaya koyması açısından önemlidir. Bu bağlamda çalışmada nitel araştırma yöntemlerinden vaka analizi kullanılmıştır. Bu araştırma türü kapsamında İkinci Karabağ Savaşı’nda Türkiye ve Rusya’nın karşı karşıya gelme biçimleri ve Türkiye’nin Azerbaycan’a verdiği desteğin araç ve yöntemleri tespit edilmiştir. Çalışmada, İkinci Karabağ Savaşı’nda Türkiye ve Rusya arasında bir rekabet yaşandığı ve bu rekabetin temel belirleyicilerinden birinin Türkiye’nin Azerbaycan’a verdiği askeri ve diplomatik destek olduğu sonucuna varılmıştır. Bu doğrultuda çalışmada tarafların resmi makamları tarafından yayınlanan belgeler ve ülkelerin üst düzey yetkililerinin açıklamaları gibi birincil kaynakların yanı sıra literatürde yer alan diğer süreli yayınlar gibi ikincil kaynaklar da kullanılmıştır.
Ankara ve Moskova Kafkasya’da Karşı Karşıya: İkinci Karabağ Savaşı’nda Türkiye’nin Azerbaycan’a Desteği ve İkilinin Stratejik Kazanımları
Keywords: International Politics; Uluslararası Siyaset